187k views
5 votes
f(x) = 3.13 + 4.02 – 82 - 2 g(x) = 3.1 - 5 Find (f - g)(). A. (f - g)(x) = 3.23 + 4x2 11x +3 B. (f - g)(x) = 3r3 + 4.22 - 112 - 7 C. (f-9)() = 3x3 + 4x² – 5x + 3 O D. (f -9)(x) = 3.2 + 4x 52 – 7

f(x) = 3.13 + 4.02 – 82 - 2 g(x) = 3.1 - 5 Find (f - g)(). A. (f - g)(x) = 3.23 + 4x-example-1
User Cyndi
by
4.9k points

1 Answer

7 votes

The given functions are -


\begin{gathered} f(x)=3x^3+4x^2-8x-2 \\ g(x)=3x-5 \end{gathered}

To find (f-g)(x) we just have to subtract the functions.


\begin{gathered} (f-g)(x)=(3x^3+4x^2-8x-2)-(3x-5) \\ (f-g)(x)=3x^3+4x^2-8x-2-3x+5 \\ \end{gathered}

At last, we reduce like terms.


(f-g)(x)=3x^3+4x^2-11x+3

Therefore, the right answer is A.

User TutuGeorge
by
5.3k points